Attacks on single-pass confidentiality modes of operation - Markowitch, Olivier; Nakahara Jr, Jorge (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2014: Anais do XIV Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2014.20123, 2014)
The main contributions of this paper are efficient distinguishing attacks against block ciphers that are conventionally modeled as pseudorandom permutations (PRP). Formally, block ciphers operate on fixed-length blocks of n bits, for example, n = 128 for the Advanced Encryption Standard (AES). Our analysis takes place in the setting in which the messages are m bits long, representing the entire input plaintext, where m is variable and unrelated to n. We show distinguish-fromrandom attacks for any n-bit block cipher in the standard modes of operation for confidentiality: ECB, CBC, CFB, OFB, CTR and XTS. We demonstrate that in all these 1-pass modes any n-bit block cipher leaves 'footprints' that allows an adversary to efficiently (in time and memory) distinguish them from a random permutation. We claim that two passes (in opposite directions) over the m-bit message, with textdependent feedforward (chaining) and in streaming mode are sufficient to circumvent the presented attacks.